Extraction and Characterization of Allamanda cathartica - Manogaran, S.; Sulochana, N. (Asian Journal of Chemistry, 2016)
The flowers of Allamanda cathartica were analyzed phytochemically and the compound was isolated from ethyl acetate extract employing chromatographic techniques. The compound was characterized by chemical and spectral methods to be flavonols and it was found to be quercetin 3-O-(6"-O-acetyl)neohesperidoside.